Sinergitas Kinerja Lintas Sektoral Dalam Penanggulangan Penyakit Mulut Dan Kuku Pada Ternak Sapi Di Kabupaten Ngawi - Wahyu Wibowo, Raden Agung Kusumo (Manajemen Agribisnis: Jurnal Agribisnis, 2025)
This research aims to describe the synergy of cross-sectoral performance in controlling foot and mouth disease in cattle in Ngawi Regency. The research was carried out from October 2023 to April 2024. Mantingan District was chosen as the research location with the assumption that the population of beef cattle is large compared to other regions and is a border area with Central Java. Steps in cross-sectoral performance synergy in overcoming foot-and-mouth disease in cattle in Ngawi Regency, formulating the focus of this research: How is cross-sectoral performance synergy in overcoming foot-and-mouth disease in cattle in Ngawi Regency? The direction of this research is expected to produce: Knowing the synergy of cross-sectoral performance in controlling foot and mouth disease in cattle in Ngawi Regency. It is hoped that the series of research processes leading to the writing of this thesis will provide benefits for the many parties involved in it. The benefits of research are divided into two types, namely theoretical and practical. As knowledge of cross-sectoral performance synergy in overcoming foot and mouth disease in cattle in Ngawi Regency. This research process hopes that all parties involved directly or indirectly can see and understand that each region has a local policy in dealing with foot and mouth disease